2018
DOI: 10.1080/19490976.2018.1465157
|View full text |Cite
|
Sign up to set email alerts
|

The human gut microbiota: Metabolism and perspective in obesity

Abstract: The gut microbiota has been recognized as an important factor in the development of metabolic diseases such as obesity and is considered an endocrine organ involved in the maintenance of energy homeostasis and host immunity. Dysbiosis can change the functioning of the intestinal barrier and the gut-associated lymphoid tissues (GALT) by allowing the passage of structural components of bacteria, such as lipopolysaccharides (LPS), which activate inflammatory pathways that may contribute to the development of insu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

11
401
2
21

Year Published

2019
2019
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 408 publications
(435 citation statements)
references
References 117 publications
(133 reference statements)
11
401
2
21
Order By: Relevance
“…The decreased blood fat may be because the probiotic removed CHO by binding it to cellular surfaces and promoting its excretion. In previous research, we found that heat‐killed cells of LIP‐1 showed higher CHO removal from media than other strains did . Meanwhile, our previous studies have shown that some gut bacteria (namely Bacteroides , Clostridium , Eubacterium , Escherichia , and Lactobacillus ) were increased in rats given LIP‐1 cells, which were known to deconjugate bile salts in the gut and enhance CHO excretion .…”
Section: Discussionmentioning
confidence: 92%
“…The decreased blood fat may be because the probiotic removed CHO by binding it to cellular surfaces and promoting its excretion. In previous research, we found that heat‐killed cells of LIP‐1 showed higher CHO removal from media than other strains did . Meanwhile, our previous studies have shown that some gut bacteria (namely Bacteroides , Clostridium , Eubacterium , Escherichia , and Lactobacillus ) were increased in rats given LIP‐1 cells, which were known to deconjugate bile salts in the gut and enhance CHO excretion .…”
Section: Discussionmentioning
confidence: 92%
“…Nowadays, it was proved that the gut microbiome is different between obese and non‐obese individuals. The intestinal dysbiosis would alter the lipid metabolism of the host, which leads to obesity . The intestinal microbial structure and composition could shift rapidly due to a diet such as the HFD, and the transit time was on average 2–3 days only in humans .…”
Section: Discussionmentioning
confidence: 99%
“…Numerous studies have reported that high sodium intake leads to a higher risk of stomach cancer, hypertension, osteoporosis, and cardiovascular disease in humans. Also, intestinal dysbiosis (changes in gut microbiota composition) affects inflammation by constant exposure of mucosal‐associated lymphoid tissue, which leads to prevalence of pathogens . Mucosal damage induced by salt and salted food may increase the possibility of persistent infection with Helicobacter pylori , and restricting salt and salted food intake can reduce the risk of gastric cancer .…”
Section: Discussionmentioning
confidence: 99%